Asian American evangelical churches : race, ethnicity, and assimilation in the second generation - Alumkal, Antony William, 1969- (New Americans (LFB Scholarly Publishing LLC), 2003)
Alumkal examines the beliefs and life experiences of American-born/raised Asian American evangelicals in two congregations, one Chinese American and one Korean American, near New York City. He documents how the culture of American evangelicalism has shaped the worldviews of its second-generation Asian American adherents. The religious beliefs of the individuals in this study were indistinguishable from those of most white evangelicals. These individuals also affirmed the view that Christian identity transcends racial/ethnic lines. Yet, paradoxically, they testified to the significance of race and ethnicity in their lives and saw their churches as places to strengthen ethnic ties. In conclusion, scholars need new theoretical approaches for understanding the post-1965 immigrants and their offspring.